Marital status, educational attainment, and suicide risk: a Norwegian register-based population study - Carine Øien-Ødegaard; Lars Johan Hauge; Anne Reneflot (BMC, 2021)
Abstract Background The presence and quality of social ties can influence suicide risk. In adulthood, the most common provider of such ties is one's partner. As such, the link between marital status and suicide is well-documented, with lower suicide risk among married. However, the association between marital status and educational level suggest that marriage is becoming a privilege of the better educated. The relationship between educational attainment and suicide is somewhat ambiguous, although several studies argue that there is higher suicide risk among the less educated. This means that unmarried with low education may concurrently experience several risk factors for suicide. However, in many cases, these associations apply to men only, making it unclear whether they also refer to women. We aim to investigate the association between marital status, educational attainment, and suicide risk, and whether these associations differ across sexes. Methods Our data consist of Norwegian residents aged 35-54, between 1975 and 2014. Using personal identification-numbers, we linked information from various registers, and applied event history analysis to estimate suicide risk, and predicted probabilities for comparisons across sexes. Results Overall, associations across sexes are quite similar, thus contradicting several previous studies. Married men and women have lower suicide risk than unmarried, and divorced and separated have significant higher odds of suicide than never married, regardless of sex. Low educational attainment inflates the risk for both sexes, but high educational attainment is only associated with lower risk among men. Being a parent is associated with lower suicide risk for both sexes. Conclusions Higher suicide risk among the divorced and separated points to suicide risk being associated with ceasing of social ties. This is the case for both sexes, and especially those with low educational attainment, which both healthcare professionals and people in general should be aware of in order to promote suicide prevention.